Critical Role of Ti4+ in Stabilizing High‐Voltage Redox Reactions in Li‐Rich Layered Material. Issue 32 (1st July 2021) - Cho, Moses; Song, Seok Hyun; Hong, Seokjae; Kim, Kyoung Sun; Avdeev, Maxim; Yoo, Jong‐Gyu; Ko, Kyung‐Tae; Hong, Jihyun; Kim, Jongsoon; Lee, Seongsu; Kim, Hyungsub
Abstract: Li‐rich layered oxide materials are considered promising candidates for high‐capacity cathodes for battery applications and improving the reversibility of the anionic redox reaction is the key to exploiting the full capacity of these materials. However, permanent structural change of the electrode occurring upon electrochemical cycling results in capacity and voltage decay. In view of these factors, Ti 4+ ‐substituted Li2 IrO3 (Li2 Ir0.75 Ti0.25 O3 ) is synthesized, which undergoes an oxygen redox reaction with suppressed voltage decay, yielding improved electrochemical performance and good capacity retention. It is shown that the increased bond covalency upon Ti 4+ substitution results in structural stability, tuning the phase stability from O3 to O1′ upon de‐lithiation during charging compared with O3 to T3 and O1 for pristine Li2 IrO3, thereby facilitating the oxidation of oxygen. This work unravels the role of Ti 4+ in stabilizing the cathode framework, providing insight for a fundamental design approach for advanced Li‐rich layered oxide battery materials. Abstract : Present findings unravel the elemental understanding of anionic redox triggering mechanism and its correlated structural stability via the Ti 4+ doped Li2 IrO3 system, in which Ti 4+ acts as a stabilizer and a promoter in Li‐rich layered oxide materials, inducing oxygen oxidation reaction at high voltage region along with suppressed voltage decay, prompting the improved electrochemical performance with better capacity retention.